Political Parties, Clientelism, and Bureaucratic Reform - Cesi Cruz; Philip Keefer (Inter-American Development Bank (IDB), 2015)
The challenge of public administration reform is well-known: politicians often have little interest in the efficient implementation of government policy. Using new data from 439 World Bank public sector reform loans in 109 countries, we demonstrate that such reforms are significantly less likely to succeed in the presence of non-programmatic political parties. Earlier research uses evidence from a small group of countries to conclude that clientelistic politicians resist reforms that restrict their patronage powers. We support this conclusion with new evidence from many countries, allowing us to rule out alternative explanations, including the effect of electoral and political institutions. We also examine reforms that have not been the subject of prior research: those that make public sector financial management more transparent. Here, we identify a second mechanism through which non-programmatic parties undermine public sector reform: clientelistic politicians have weaker incentives to exercise oversight of policy implementation by the executive branch.
hdl:11319/6968
Keywords: D72; D73; H41; H83; 330; Clientelism; political parties; public sector reform